UPAYA MENINGKATKAN HASIL BELAJAR MATEMATIKA PADA MATERI PERKALIAN DENGAN METODE JARIMATIKA SISWA KELAS V DI SD NEGERI 2 METRO TIMUR - Melinda Noviana; Najla Hwaida Arnito; Niken Larasati; Finorina; Roli Fola Cahya Hartawan (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2025)
Various factors can cause students to have difficulty in working on multiplication problems, one of which is the teacher's teaching method. Therefore, teachers need to teach the material in a way that is easy to understand and fun. To improve mathematics learning outcomes in multiplication material in grade V of SD Negeri 2 Metro Timur, it is important to emphasize the use of methods that can help students understand and solve multiplication problems more easily. The application of methods that make it easier for students and use concrete tools that are easy to find is very necessary. This aims to ensure that the mathematics learning objectives set in the curriculum can be achieved in accordance with students' cognitive development. One method that is considered effective in improving numeracy skills while also raising enthusiasm for learning is the jarimatika method. This method uses 10 fingers as aids in the multiplication calculation process. With the jarimatika method, students do not need to buy additional teaching aids because this method is very practical and only relies on their fingers as a medium for counting. Every student has fingers, so this method is in line with their cognitive development stage. Through this method, students can more easily understand the concept of multiplication while engaging in physical activities that are relevant to the material being studied.